FAHREDDİN RAZI’S COMMENTS ON THE INFORMING ATTRIBUTES OF ALLAH - Abdullah ARCA (Fırat University, 2019)
Allah, in some verses of Quran, used various expressions which are peculiar to the creatures for himself . The prophet also depicted Allah with the same terms in his sayings. The misperception of such expressions used in Quran and Hadith paved the way for false depictions of Allah in some Kalam schools. Mushabbihah, Mucassimah and those who thought in the same way understood those expressions used in Quran and Hadith in their literal meaning and likened Allah to the creatures. On the other hand, Cehmiyye, Mutezilah and a great majority of Sunnah scholars kept attributes regarding creation away from Allah. They emphasized that these expressions used in Quran and Hadith should be interpreted in a way worthy of Allah’s glory. The aim of this article is to bring to light the ideas of Fahreddin Razi, who is one of the most preeminent figures of Kalam discipline, on informing attributes, the method he used to make these attributes understood correctly and his comments related to this subject. While on the one hand he criticised and opposed to the misbeliefs of schools such as Haşeviyye ve Kerramiyye, which had the concept of comparision (teşbih) and embodiment (tecsim) regarding Allah’s informing attributes, on the other hand he asserted that new meanings be given to expressions bearing attributions to creatures in Quran and Hadith in order to settle correct conception of Allah in accordance with tenzih belief in minds. Razi proved the impossibility of using each informing attribute in their literal meaning with intellectual and logical proofs and interpretations and helped place the belief of Allah in Muslim’s minds in a right way.